Dampak Literasi Halal Food dan Kesadaran Sertifikasi Halal terhadap Keputusan Pembelian Korean Food : Studi Kasus Generasi Z - Zenita Alvina Fauziah; Risma Syan Sabilla; Rifa Khoerunnisa; Lina Marlina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The lifestyle of Indonesian society, especially among Generation Z, has been influenced by globalization and foreign popular culture, specifically the Korean wave or hallyu. Awareness of halal certification and knowledge and literacy about halal food are important to study as they influence Generation Z's purchasing decisions regarding Korean food. This study uses a descriptive method, namely a qualitative approach, while the type of research used is literature research in the form of books, interpretations of the Qur'an, Hadith, and others related to the problem to be solved. Halal food is food and drink that is permissible for consumption according to Islam, i.e., free from haram ingredients such as pork, meat from animals that have not been slaughtered in accordance with Islamic law, and alcohol. To determine whether food is haram, there needs to be a guarantee, such as a halal certificate, which is an absolute step to ensure that a product complies with applicable standards. Korean food is cuisine that has grown and developed from the Korean environment and culture, which has a unique taste, starting from the names of the dishes, which are able to attract the interest of the public, especially Generation Z.